A Bibiliometric Analysis of Microfinance Studies - Adhi Setyo Santoso (President University, 2017)
Abstract Microfinance is a social entrepreneurship related topic that gained the academic researchers’ attention in the past 10 years because of its adoption in the less developed financial access area. The article aims to map the previous research direction and provide the guidance for further research by conducting a bibilometric analysis from SCOPUS database with co-citation analysis technique. There are 2077 published articles in the SCOPUS indexed journal within 1996 – 2016. Among these articles, we analyzed 90 articles that have 10 co-citations or more. The results shows that there are 3 main clusters in microfinance studies including the impact of microfinance in developing countries, strategic management and organizational behavior of microfinance, and the economic of microfinance The future research direction is discussed in the concluding remarks section. Keywords: Microfinance, social entrepreneurship, microlending, bibilometric analysis, co-citation analysis, areas of knowledge